2016
DOI: 10.1071/wf16021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesising empirical results to improve predictions of post-wildfire runoff and erosion response

Abstract: Abstract. Advances in research into wildfire impacts on runoff and erosion have demonstrated increasing complexity of controlling factors and responses, which, combined with changing fire frequency, present challenges for modellers. We convened a conference attended by experts and practitioners in post-wildfire impacts, meteorology and related research, including modelling, to focus on priority research issues. The aim was to improve our understanding of controls and responses and the predictive capabilities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
0
27
1
Order By: Relevance
“…A substantial body of hydrological research exists on fire impacts on soil‐, hillslope‐ and, to a lesser extent, catchment‐scale processes with a focus on infiltration, runoff, erosion, and water yield (Moody, Shakesby, Robichaud, Cannon, & Martin, ; Shakesby & Doerr, ; Shakesby, Moody, Martin, & Robichaud, ). However, despite the concerns highlighted above, research has only recently focused on linkages between on‐site and downstream impacts of fire on water quality (Abraham, Dowling, & Florentine, ; Bladon, Emelko, Silins, & Stone, ; Smith, Sheridan, Lane, Nyman, & Haydon, ) and treatability of contaminated water following fire (Emelko, Silins, Bladon, & Stone, ).…”
Section: The Challengementioning
confidence: 99%
See 1 more Smart Citation
“…A substantial body of hydrological research exists on fire impacts on soil‐, hillslope‐ and, to a lesser extent, catchment‐scale processes with a focus on infiltration, runoff, erosion, and water yield (Moody, Shakesby, Robichaud, Cannon, & Martin, ; Shakesby & Doerr, ; Shakesby, Moody, Martin, & Robichaud, ). However, despite the concerns highlighted above, research has only recently focused on linkages between on‐site and downstream impacts of fire on water quality (Abraham, Dowling, & Florentine, ; Bladon, Emelko, Silins, & Stone, ; Smith, Sheridan, Lane, Nyman, & Haydon, ) and treatability of contaminated water following fire (Emelko, Silins, Bladon, & Stone, ).…”
Section: The Challengementioning
confidence: 99%
“…Despite their economic and environmental significance, it is still difficult to sufficiently predict the probability and magnitude of post-fire contaminant exports to enable (a) reliable water contamination risk assessments in fire-prone catchments and (b) support effective mitigation strategies (Shakesby, 2011;Shakesby et al, 2016;Verkaik et al, 2013). Research in this area has recently gained momentum, but the body of research is still relatively small with enormous variability in the reported drivers of post-fire contamination events (type of pollutants and mobilization processes; Moody et al, 2013) and location-or end user-specific questions (e.g., White et al, 2006;Emelko et al, 2011;Campos et al, 2012;Santín, Doerr, Otero, & Chafer, 2015;Santos, Sanches Fernandes, Pereira, Cortes, & Pacheco, 2015a, 2015bLanghans et al, 2016).…”
Section: The Challengementioning
confidence: 99%
“…Modelling tools exist to distinguish wildland fire impacts from climate impacts . The efficiency and reliability of risk assessment tools will rely on the continued improvement of models of mesoscale climate patterns (Jones, Nyman, & Sheridan, 2014;Moody et al, 2016;Shakesby, Moody, Martin, & Robichaud, 2016). Regional climate change is expected to lead to higher precipitation variability and evapotranspiration across the United States and possibly higher fire potential after 2040 (Duan et al, 2016;Liu, Goodrick, & Stanturf, 2013).…”
Section: Prescribed Fire Impacts On Streamflowmentioning
confidence: 99%
“…The reduction of vegetation and ground cover by wildfires increases soil susceptibility to raindrop impact. This physical process, together with the soil physical and chemical alteration by heating, may reduce aggregate stability and promotes sediment detachment and transport by water (Certini, ; Esteves et al, ; Moody, Shakesby, Robichaud, Cannon, & Martin, ; Prats, dos Santos Martins, Malvar, Ben‐Hur, & Keizer, ; Santín & Doerr, ; Shakesby, ; Shakesby & Doerr, ; Shakesby, Moody, Martin, & Robichaud, ). Wildfires can further induce the occurrence of soil water repellency (Keizer et al, ; Shakesby, ), leading to an increased hydrological response and soil erosion (Fernández, Vega, & Vieira, ; Vieira, Malvar, Fernandez, Serpa, & Keizer, ).…”
Section: Introductionmentioning
confidence: 99%